1984
DOI: 10.1128/iai.44.2.292-298.1984
|View full text |Cite
|
Sign up to set email alerts
|

Human serum antibody response to Campylobacter jejuni infection as measured in an enzyme-linked immunosorbent assay

Abstract: An enzyme-linked immunosorbent assay was adapted to measure immunoglobulin A (IgA), IgG, and IgM classes of human serum antibody to Campylobacterjejuni. Sera were tested from healthy controls, from ill persons at various intervals after exposure to an epidemiologically implicated vehicle for Campylobacter sp. enteritis, from persons exposed to these same vehicles who remained well, and from persons who chronically drank raw milk. The major antigens in the C. jejuni acid-washed antigen preparations from three d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
57
0
1

Year Published

1987
1987
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(62 citation statements)
references
References 23 publications
(20 reference statements)
3
57
0
1
Order By: Relevance
“…In this study we have investigated the kinetics, isotypes and specificity of serum and mucosal antibodies in patients following naturally acquired campylobacter infections. The results confirm [13] that acute campylobacter infections induce specific serum IgG and IgA in the convalescent phase (1 week to 2 months). In general these antibodies declined over time but the IgG antibodies, in particular, remained detectable in sera collected up to one year postinfection.…”
Section: Discussionsupporting
confidence: 84%
“…In this study we have investigated the kinetics, isotypes and specificity of serum and mucosal antibodies in patients following naturally acquired campylobacter infections. The results confirm [13] that acute campylobacter infections induce specific serum IgG and IgA in the convalescent phase (1 week to 2 months). In general these antibodies declined over time but the IgG antibodies, in particular, remained detectable in sera collected up to one year postinfection.…”
Section: Discussionsupporting
confidence: 84%
“…Because this method allows the determination of class-specific antibodies, it has been applied also in Campylobacter serology (2, 5 , 22). Several groups, including ourselves, have reported rapid changes in Campylobacter IgA and IgM antibody titers to be typical for the acute phase of campylobacteriosis (2,5,22). We have also shown fourfold or greater titer changes in paired sera of patients whose Campylobacter antibody titers otherwise had been regarded as negative (22).…”
Section: Discussionmentioning
confidence: 95%
“…Later, common antigens of campylobacters have been applied. They have included alkaline extracts in complement tests (16), pooled bacterial antigens in radio-immunoassay (12) and acid extracts (2,8,21,25) or sonicates of heated bacteria ( 5 ) in EIA.…”
mentioning
confidence: 99%
“…4b) and this protein was presumed to be responsible for either the 92-kd or 63-kd peptide. To separate the hooks from the flagellar filaments, the flagella obtained by gel filtration were suspended in dilute Amidoblack-stained electrophoretic profile of purified flagellin protein (1) and parallel immunoblot with rabbit anti-flagellin antiserum (2). The antiserum was diluted I : 200 with PBS-Tween and peroxidase-conjugated goat anti-rabbit IgG antibody was diluted 1:800.…”
Section: Ohashi and Dr T Ito Of Tokyo Metropolitan Research Laboratmentioning
confidence: 99%
“…In Campylobacter infection the flagella or motility of the bacteria are reported to play an important role in colonization of the intestinal tract (19,22). In addition, the flagellar protein of C. jejuni is highly immunogenic in humans (4) and it has been reported that there are various classes of antibodies against this protein in the convalescent sera (2,17). Therefore it is presumed that the colonization of the intestinal tract by this bacterium can be prevented by the specific antiserum for the flagella.…”
mentioning
confidence: 99%